1996
DOI: 10.1080/02724936.1996.11747833
|View full text |Cite
|
Sign up to set email alerts
|

Burns in children under 3 years of age: the Zaria experience

Abstract: This is a retrospective study of 84 children aged 36 months and less who were admitted for burns care from January 1980 to December 1989. Fifty-four (64%) had scalds, 28 (33%) had flame burns and in two children the cause was not known. The upper extremities were most commonly involved. Sixty-five per cent of the children were admitted during the cool, dry Harmattan season. Associated factors included cooking at floor level, bedside fires, epileptic fits in the mothers and general architectural factors. Wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Among studies with adults only, men are found to be more at risk especially between 20 and 30 years of age [100] , [102] , [103] , [105] , [106] . Scald injuries (usually in children) and flame injuries (usually in adults) are the most common types of injuries [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies with adults only, men are found to be more at risk especially between 20 and 30 years of age [100] , [102] , [103] , [105] , [106] . Scald injuries (usually in children) and flame injuries (usually in adults) are the most common types of injuries [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , …”
Section: Resultsmentioning
confidence: 99%
“…Several studies note specific socio-economic factors common to admitted patients. Limited education, unemployment, having more than six persons in the home and/or single room house, being from a rural area, and/or having a ‘low income’ are common among admitted patients [67] , [71] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] .…”
Section: Resultsmentioning
confidence: 99%
“…The associated morbidity, disability, socioeconomic losses, Gross National Product (GNP) and Disability Adjusted Life Year (DALY) losses have been documented by several studies [ 1 - 3 ]. Several workers have studied the causes, patterns, and outcomes of injury, and sociodemographic factors associated with injury [ 3 - 10 ]. However, few workers have described the pattern of injuries, and associated factors, in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…However, few workers have described the pattern of injuries, and associated factors, in Nigeria. Moreover, majority of these studies have been hospital-based [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Africa where an open re is regularly used for cooking (2). The sauna tradition in Finland is another example of the importance of different lifestyles for the type of burn.…”
Section: Discussionmentioning
confidence: 99%